Time Based Traffic Policing and Shaping Algorithms on Campus Network Internet Traffic - Kassim, Murizah; Ismail, Mahamod; Yusof, Mat Ikram; Abdullah, Mohd Azrul (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This paper presents the development of algorithm on Policing and Shaping Traffic for bandwidth management which serves as Quality of Services (QoS) in a Campus network. The Campus network is connected with a 16 Mbps Virtual Private Network line to the internet Wide Area Network. Both inbound and outbound real internet traffic were captured and analyzed. Goodness of Fit (GoF) test with Anderson-darling (AD) was fitted to real traffic to identify the best distribution. The Best-fitted Cumulative Distribution Function (CDF) model was used to analyze and characterized the data and the parameters. Based on the identified parameters, a new Time Based Policing and Shaping algorithm have been developed and simulated. The policing process drops the burst traffic, while the shaping process delays traffic to the next time transmissions. Mathematical model to formulate the controlled algorithm on burst traffic with selected time has been derived. Inbound traffic threshold control burst was policed at 1200 MByte (MB) while outbound traffic threshold was policed at 680 MB in the algorithms. The algorithms were varied in relation to the identified Weibull parameters to reduce the burst. The analysis shows that the higher shape parameter value that relates to the lower burst of network throughput can be controlled. This research presented a new method for time based bandwidth management and an enhanced network performance by identifying new traffic parameters for traffic modeling in Campus network.